DEIKSIS PERSONA DALAM FILM MALEFICENT: ANALISIS PRAGMATIK - PAPILAYA, YURICA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT. This study is an attempt to describe and analyze person deixis which is found in the film Maleficent. The aim of this research is to identify and classify the type, and the function of person deixis used in the film. The method used in this research is descriptive method. The data of deixis have been taken from the sentences in the film Maleficent and analyzed using Levinson’s concept. In English, there are 3 types of person deixis, those are: first person deixis, second person deixis and third person deixis. Deixis itself is a pointing term in language The result of this study shows that person deixis is classified into 3 type, those are: first person deixis: I, me, my, mine, us, our, we; second person deixis: you, your; and third person deixis: they, her, she, he him, it, its. Keywords: Person deixis, Pragmatic Analysis, Film Maleficent